La actividad física recreativa y el sedentarismo, barrio Cuarto Centenario año 2015 - Ramón Villavicencio, Cristian Geovanny (2016)
This research work is aimed to know THE ACTIVITY PHYSICAL RECREATION AND THE SEDENTARY LIFESTYLE, NEIGHBORHOOD FOURTH CENTENARY YEAR 2015. Physical activity exercise sports - recreation at moderate intensity generates benefits not only on the physical level but also at the psychic level, since it collaborates in the emotional, social, intellectual and motor development. This is why we want to show that sedentary can fight when in our daily work included such activities. This investigation took as a sign to inhabitants of the fourth centenary district. Activities physical – recreational represent today a need for people, since systematic practice and still offers you the possibility of counteracting the effects produced during the process of aging. The methodology used is framed in the form of feasible project through a descriptive field research. The design defines it as a nonexperimental research. In the investigation for the purposes of this thesis we have used some methods of research are scientific methods of induction, deduction, analysis - synthesis, historical logic and methods empirical observation and survey, theoretical methods, approach system, probability, mathematical analysis of content, cyber, empirical evidence is based on fieldwork with the support of various instruments including the interview survey that allowed us to collect data. Through the qualitative method we use interviews with open and closed questions to determine if this possible lack of realization of physical sport - recreational could reach relate to social, cultural and socio-economic problems facing individuals; to their family history; to experiences; Consequently decrease in motor skills and/or self-realization; and/or due to ignorance about the benefits arising from such ac